Task-Based Language Teaching in the Digital Era: Conceptualizing Technology-Enhanced Tasks for TESL - Muralei, Divithaa; Selvaraja, Divviya; Santiran, Nishanthi; George, Patricia; Selvaraju, Vikneshwari; Md Yunus, Melor; Hashim, Harwati; Ediyanto, Ediyanto (Semarak International Journal of Current Research in Language and Human Studies, 2025)
Technology has significantly reshaped language learning, offering new possibilities for integrating digital tools with Task-Based Language Teaching (TBLT). While TBLT is widely recognised for its effectiveness in second language acquisition, it is still necessary to explore how technology can enhance its core principles and improve learning outcomes. The main challenge lies in designing, implementing, and assessing technology-enhanced tasks that align with TBLT while addressing digital literacy gaps, task complexity, and assessment validity. This conceptual paper discusses how technology enhances TBLT in Teaching English as a Second Language (TESL). It explores theoretical models and frameworks that support technology-mediated tasks, such as online simulations, gamified learning, and collaborative digital activities. Using a critical analysis of existing literature, this paper aims to identify key benefits, challenges, and best practices concerning Technology-Enhanced Tasks with TBLT. This paper will provide insights into how technology could support language acquisition in task-based learning environments by synthesising current research. It will also highlight areas for further investigation, particularly in task design, assessment strategies, and teacher training. The paper contributes to the ongoing discussion on enhancing digital tools for language education, ensuring that technology serves as an effective complement to the TBLT approach.